Economic status, a salient motivator for medicalisation of FGM in sub-Saharan Africa: Myth or reality from 13 national demographic health surveys - Imran O. Morhason-Bello; Adeniyi Francis Fagbamigbe; Yusuf Olushola Kareem; Oladosu A. Ojengbede (Elsevier, 2020)
Female Genital Mutilation or Cutting (FGM) and its medicalisation remain a challenge in sub-Sahara African (SSA). Early identification of at-risk women might help in instituting focused counselling against FGM medicalisation. We hypothesised that the risk of medicalised FGM by girls/women is associated with socioeconomic status (SES) their household belongs.We used 2010-2019 Demographic and Health surveys data from 13 countries in SSA. We analysed information on 214,707 women (Level 1) nested within 7299 neighbourhoods (Level 2) from the 13 countries (Level 3). We fitted 5 multivariable binomial multilevel logistic regression models using the MLWin 3.03 module in Stata. The estimation algorithms adopted was the first order marginal quasi-likelihood linearisation using the iterative generalised least squares.The odds of FGM medicalisation increased with the wealth status of the household of the woman, with 29%, 45%- and 75%-times higher odds in the middle, richer and richest household wealth quintiles, respectively than those from the poorest households (p < 0.05). The more educated a woman and the better a woman's community SES was, the higher her odds of reporting medicalisation of FGM. Rural community was associated with higher odds of medicalised FGM than urban settings.Medicalised FGM is common among women from a high socioeconomic, educational background and rural settings of SSA. We recommend a culturally sensitive policy that will discourage perpetuation of FGM, particularly by healthcare providers. Future studies should focus on identifying drivers of FGM among the high social class families in the society in SSA.